Մաշտոցի ուղևորությունը Բյուզանդիա. Կորյունի բնագիրը և պատմական հանգամանքները - Վարդազարյան, Օլգա
The information about Early Byzantine realities, in particular, about the organization of the “state post office,” allows us reconstructing some details of Mashtots’s trip to Byzantium։ the probable route (Dvin/Vagarshapat – Bagavan – Tigranakert – Amida – Melitene – Arabissos – Caesarea – Ancyra – Nicomedia – Constantinople), the type of transport (angaria – a covered four-wheeled heavy cart drawn by oxen), the duration of the trip (10-12 months), the officials involved in granting the permission for the use of cursus publicus, and in general, responsible for the entire visit (Dux Armeniae and the head of his office, Magister officiorum). On the basis of this information, the author proposes the correction “an[g]arwoy” in Koriwn’s text (from angaria) and explains the reason for the small number of Mashtots’s companions on his way from Melitene to Constantinople (the limited holding and carrying capacity of the wagon). Сведения о ранневизантийских реалиях, в частности, об организации “государственной почты”, позволяют реконструировать некоторые детали путешествия Маштоца в Византию։ вероятный маршрут (Двин/Вагаршапат – Багаван – Тигранакерт – Амида – Мелитена – Арабиссос – Кесария – Анкира – Никомидия – Константинополь), тип транспорта (angaria – крытая четырехколесная тяжелая повозка, запряженная волами), длительность путешествия (10-12 месяцев), круг должностых лиц, причастных к выдаче патента на пользование “дромосом”, и вообще, ответственных за весь ход визита (дукс Армении и начальник его канцелярии, магистр оффиций). На основании этих сведений в тексте Корюна предлагается конъектура an[g]arwoy (из angaria), а также объясняется малочисленность маштоцевских спутников на пути из Мелитены в Константинополь (ограниченная вместимость и грузоподъемность повозки).
Keywords: Պատմություն; Մեսրոպ Մաշտոց